1984
DOI: 10.1136/bjo.68.5.329
|View full text |Cite
|
Sign up to set email alerts
|

Central serous chorioretinopathy complicating systemic corticosteroid treatment.

Abstract: A 39-year-old man was admitted to our hospital with acute bilateral RBN of unknown origin. His corrected vision was 0 4 OD and 0*01 OS. Ophthalmoscopic examination was normal except for a few small subretinal yellowish dots in the right macular area. There was a past history of CSR in the right eye. Corticosteroid treatment with betamethasone 10 mg per day in 500 ml of 5% glucose was started. This was a high initial dosage but was thereafter gradually reduced. On the sixth day of therapy, when the steroid dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
6

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 3 publications
3
81
0
6
Order By: Relevance
“…Several cases in the literature demonstrate improvement of CSR following discontinuation or reduction of exogenous steroids (41)(42)(43)(44)(45)(46). Furthermore, other reports demonstrate recurrence of CSR with subsequent steroid treatment courses or increases in steroid dose (47,48). This also correlates with resolution in the 2 patient cases described in this article.…”
Section: Treatmentsupporting
confidence: 57%
“…Several cases in the literature demonstrate improvement of CSR following discontinuation or reduction of exogenous steroids (41)(42)(43)(44)(45)(46). Furthermore, other reports demonstrate recurrence of CSR with subsequent steroid treatment courses or increases in steroid dose (47,48). This also correlates with resolution in the 2 patient cases described in this article.…”
Section: Treatmentsupporting
confidence: 57%
“…Central serous chorioretinopathy is more prevalent in endogenous hypercortisolism and occurs in patients receiving corticosteroid therapy. 2,4 Rapid onset of chorioretinopathy within a month of starting therapy with a total minimum dosage of 200 mg of prednisolone has been reported. 5 Rare variants of central serous chorioretinopathy with chronic, bilateral, extrafoveal, multifocal, and bullous retinal detachments have been observed in patients undergoing cardiac transplantation.…”
Section: Commentmentioning
confidence: 99%
“…2 Although the pathophysiology remains controversial, most agree that increased choroidal vascular permeability is a prerequisite. 2,3 It has further been suggested that choroidal ischaemia may be the primary event responsible for the altered permeability.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,5 Use of glucocorticoids has been repeatedly found to be a risk factor for CSC, and their discontinuation is recommended when this diagnosis is made. 1,2,6,7 When SRF persists and VA deteriorates, treatment is considered, most commonly with verteporfin photodynamic therapy (PDT), which is the most extensively studied treatment modality for CSC. 1,[8][9][10] The pathophysiology of CSC has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%